Answer:
210
Step-by-step explanation:
if you divide 126 by 3 you get 42 than multiply by 5 and you get 210
.Given:
![\begin{gathered} f(x)=-x+1 \\ g(x)=x^2-2x-1 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20f%28x%29%3D-x%2B1%20%5C%5C%20g%28x%29%3Dx%5E2-2x-1%20%5Cend%7Bgathered%7D)
ToDetermine: The value of
![f(1)+g(2)](https://tex.z-dn.net/?f=f%281%29%2Bg%282%29)
Solution
![\begin{gathered} f(x)=-x+1 \\ f(1)=-1+1 \\ f(1)=0 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20f%28x%29%3D-x%2B1%20%5C%5C%20f%281%29%3D-1%2B1%20%5C%5C%20f%281%29%3D0%20%5Cend%7Bgathered%7D)
![\begin{gathered} g(x)=x^2-2x-1 \\ g(2)=(2)^2-2(2)-1 \\ g(2)=4-4-1 \\ g(2)=-1 \\ f(1)+g(2)=0+(-1) \\ f(1)+g(2)=-1 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20g%28x%29%3Dx%5E2-2x-1%20%5C%5C%20g%282%29%3D%282%29%5E2-2%282%29-1%20%5C%5C%20g%282%29%3D4-4-1%20%5C%5C%20g%282%29%3D-1%20%5C%5C%20f%281%29%2Bg%282%29%3D0%2B%28-1%29%20%5C%5C%20f%281%29%2Bg%282%29%3D-1%20%5Cend%7Bgathered%7D)
Hence, f(1) + g(2) = -1
the gym teacher has lots of wood
Step-by-step Sorry I got this from the book and it’s the real answer
Answer:
ni had this yesterday hold up gotta find answer